Discovery of a bright microlensing event with planetary features towards the Taurus region: a super-Earth planet. Issue 3 (21st February 2018) - Nucita, A A; Licchelli, D; De Paolis, F; Ingrosso, G; Strafella, F; Katysheva, N; Shugarov, S
Abstract: The transient event labelled as TCP J05074264+2447555 recently discovered towards the Taurus region was quickly recognized to be an ongoing microlensing event on a source located at distance of only 700–800 pc from Earth. Here, we show that observations with high sampling rate close to the time of maximum magnification revealed features that imply the presence of a binary lens system with very low-mass ratio components. We present a complete description of the binary lens system, which host an Earth-like planet with most likely mass of 9.2 ± 6.6 M⊕ . Furthermore, the source estimated location and detailed Monte Carlo simulations allowed us to classify the event as due to the closest lens system, being at a distance of ≃380 pc and mass ≃0.25 M⊙ .